RANCANG BANGUN AUGMENTED REALITY (AR) BERBASIS ANDROID UNTUK PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA - Asep Mahpudin; Evan Farhan Wahyu Puadi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This research has stages of research (1) Making Concepts Preparing Physics lesson material that will be developed through the implementation of Androidbased Augmented Reality (AR) technology, (2) Designing an Android-based Augmented Reality (AR) technology for developing Physics learning media, (3 ) Product Design of Android-based Augmented Reality (AR) Technology for the Development and Innovation of Physics Learning Media, (4) Product Validation, (5) Revision of Android-Based Augmented Reality (AR) Technology, (6) Trial of Augmented Reality Technology Products (AR ) Based on Android for theDevelopment and Innovation of Physics Learning Media, (7) Android-Based Augmented Reality (AR) Application for Physics Learning Media Development and Innovation. The subject of this research is the development of innovative physics learning media through the implementation of Android-based Augmented Reality technology, and the object of research is the students of SMAN 1 Jalaksana. The development of innovative physics learning media aims to providebetter understanding of physical concepts. From the results of non-parametric trials using Wilcoxon, the results for the experimental and control classes concluded that α> p-value. The experimental class obtained a p-value of 0.002 with α = 0.05, while the control class obtained a p-value of 0.002. So that from the results of these tests after learning is carried out experimental class is better than the control class significantly, meaning that learning by using media influences students' understanding ability Keywords: Technology Augmented Reality (AR), Android, Physics Learning